British Foreign Policy and the Anglican Church: Christian Engagement with the Contemporary World - Hyde-Price, Adrian (Ashgate Publishing Ltd, 2008)
This book seeks to elucidate whether there are particular Christian perspectives on the role that Great Britain should play in the world today. It investigates the role that the Church of England has played in contemporary foreign policy issues: including the use of force - intervention, counter-terrorism and arms sales - and overseas trade, aid and debt forgiveness. The book brings together senior individuals from within the Church, academia and non-governmental organizations to investigate these various ethical dilemmas.